Analysis of Positive Legal Sources on the Implementation Bugis Customary Sanctions of Makassar for Silariang Actor - Salle Salle; Mirnawanti Wahab (JURNAL AKTA, 2022)
In this study, the researchers analysed the phenomenon of Silariang (embarrassed) practice in the life of the Bugis Makassar society, which was considered unsuitable with the values of traditional life. This research aims to find out the form of Silariang according to Makassar Bugis customary law and implement a customary penalty for Silariang perpetrators. The research method used is juridical-normative with a statutory approach and a conceptual approach. The results of this study indicate that, according to Makassar Bugis customary law, Silariang or elopement is found in the Makassar community and can be found in other ethnic traditions outside Makassar. What makes them different is the punishment applied to the two perpetrators. For other ethnic groups, the penalty is usually not so severe. However, for the Makassarese, it usually ends with the murder of the perpetrator. The implementation of this customary law punishment is in the form of humiliation or persecution, expulsion from the village, and even the death penalty if the violation is very serious. The only one who can carry out the punishment is the family who does the Silariang. Also, the results of other studies illustrate that the embodiment of customary law principles as part of a positive legal source in Indonesia is highly recommended. Moreover, in the context of upholding morality, cultural nobility, honesty, and justice, it should avoid legal dilemmas to enforce the law against the law. After that, all decisions of legal action are aimed at creating public order, balance, and peace. Legal decisions based on the paradigm of customary law in the Silariang can cause feelings of shame, hurt, and revenge, ending in revenge efforts.